Konsep Etika al-Haya' dan al-'Iffah dalam Perspektif Hadis: Analisis Fenomena Live Mengemis di TikTok: The Concepts of al-Ḥayāʾ and al-ʿIffah in the Hadith Perspective: An Analysis of the Live Begging Phenomenon on TikTok - Mohammad Gymnastiar Setyawan; Salman Zulfami (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This study aims to analyze the phenomenon of live begging on the TikTok platform from the perspective of hadith, using the ethical framework of al-haya`(modesty) and al-`iffah(preserving one’s dignity). This study employs a qualitative method with a literature review approach, analyzing hadith texts and related literature through a descriptive-conceptual analysis. The results indicate that TikTok’s live streaming and virtual gifting features have given rise to a new pattern of interaction known as e-begging or digital begging. This practice manifests in various forms, such as the dramatization of sorrow, extreme actions for the sake of gifts, the exploitation of vulnerable groups, and open requests for gifts. From a hadith perspective, the act of displaying suffering for economic gain contradicts the principle of al-haya`as a moral regulator, as well as the value of al-‘al-`iffah, which emphasizes self-respect, economic independence, and the prohibition against begging unless in an emergency. This study concludes that the phenomenon of live begging not only represents a socio-economic issue but also indicates moral and spiritual degradation in the digital space. Furthermore, awareness of hadith values is crucial as a filter in digital ethics to prevent Muslims from compromising their dignity.